2009
DOI: 10.1007/s10490-009-9152-5
|View full text |Cite
|
Sign up to set email alerts
|

Do you really need help? A study of employee supplication and job performance in China

Abstract: Supplication, Impression management, Social role theory,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
3
12
0
Order By: Relevance
“…Finally, Rico Lam and colleagues (Lai, Lam, & Liu, 2010) examine how employee supplication, or making oneself vulnerable to a boss or decision-maker, impacts employee job performance. They use 158 supervisor-subordinate dyads in China to test hypotheses related to supplication.…”
Section: Empirical Papersmentioning
confidence: 99%
“…Finally, Rico Lam and colleagues (Lai, Lam, & Liu, 2010) examine how employee supplication, or making oneself vulnerable to a boss or decision-maker, impacts employee job performance. They use 158 supervisor-subordinate dyads in China to test hypotheses related to supplication.…”
Section: Empirical Papersmentioning
confidence: 99%
“…Lai, Lam, and Liu (2012), presenting their research on supervisor -employee relationships, found confirmation for the following 'helping' hypothesis: in Chinese organizations, 'consistent with social role theory, the normative expectation of helping others in need should be stronger for longer-tenured employees [ready] to assume a nurturing role in the organization' (12). Those in positions of authority who are better established have both a role expectation and a moral obligation to help junior colleagues.…”
Section: Consideration Of Simmonsmentioning
confidence: 95%
“…Those in positions of authority who are better established have both a role expectation and a moral obligation to help junior colleagues. The authors posit that, in China, these role-bound normative expectations are tied to exemplary traditional values of loyalty and reciprocity, Confucian models of social relationships which have continued purchase today (Lai, Lam, and Liu 2012).…”
Section: Consideration Of Simmonsmentioning
confidence: 99%
“…Research has shown that status cannot be achieved merely through coercion, but also through self-sacrifice (Griskevicius, Tybur, & Van den Bergh, 2010), charm (Stevens, Deuling, & Armenakis, 2012), and emotional manipulation (Flynn, Reagans, Amanatullah, & Ames, 2006;Grieve, 2011). Whereas some manipulative self-presentation (i.e., intimidation, self-promotion) is driven more by the desire to dominate, other types (i.e., supplication; ingratiation) are instrumental in nature (Appelbaum & Hughes, 1998;Lai, Lam, & Liu, 2010). As such, we expected that status seeking would relate with all self-presentation tactics.…”
Section: Workplace Self-presentationmentioning
confidence: 99%